Amyand’s hernia: A rare case report - Gujar, Sunil; Golchha, Vipul; Patel, Akhilesh Kumar; Gurwani, Siddhart; Gupta, Raunak Kumar; Shinde, Siddharth; Ninama, Sneha; Deshwali, Ankur (Indian Journal of Case Reports, 2020)
Amyand’s hernia is an atypical and rare hernia characterized by the herniation of the vermiform appendix into the inguinal sac. Here, we report the case of a 60-year-old male patient presented with complaints of the right-sided reducible inguinal hernia. On exploration as an incidental finding, we encountered an Amyand’s hernia treated with appendectomy and hernioplasty without any complications. Hence, we should keep in mind to rule out Amyand’s hernia during hernioplasty.